2010
DOI: 10.1177/000313481007600931
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Blood Loss Predicts Hemorrhage-Related Reoperation after Orthotopic Liver Transplantation

Abstract: Postoperative hemorrhage after orthotopic liver transplantation (OLT) may require early reoperative intervention. Previous studies have shown intraoperative transfusion requirement as a main determinant of reoperative intervention after OLT. The goal of this study was to develop an intraoperative hemorrhage model predicting need for reoperation after OLT. A single institution, retrospective review of adult primary OLT patients from January 2002 to 2008 was conducted. Multivariate logistical regression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Although DC with intra-abdominal packing and temporary closure has gained popularity in the treatment of patients with multisystem trauma, 4,13,21,22 hepatic trauma, [23][24][25][26][27][28][29][30][31] and nontrauma, [5][6][7]32,33 few data exist regarding its use in liver transplant, with the literature limited to case reports and small case series. [34][35][36] This study is the largest contemporary singlecenter experience with DC in liver transplant. We report graft and patient outcomes and define predictors of the need for DC.…”
Section: Discussionmentioning
confidence: 99%
“…Although DC with intra-abdominal packing and temporary closure has gained popularity in the treatment of patients with multisystem trauma, 4,13,21,22 hepatic trauma, [23][24][25][26][27][28][29][30][31] and nontrauma, [5][6][7]32,33 few data exist regarding its use in liver transplant, with the literature limited to case reports and small case series. [34][35][36] This study is the largest contemporary singlecenter experience with DC in liver transplant. We report graft and patient outcomes and define predictors of the need for DC.…”
Section: Discussionmentioning
confidence: 99%
“…The reoperation rate after LT is reported to be high, ranging from 9.2% to 34% [10] [13] , while the reoperation rate after liver resection is reported to be as low as 2.5% to 10.9% [14] [16] . In fact, at our institute, reoperations were performed for only 3 cases (2.7%) among 111 corresponding donors for biliary leakage (2 cases, 1.8%) and postoperative bleeding (1 case, 0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding risk factors for early reoperation, female sex, Child-Pugh class C, Non-HCV etiology, fulminant hepatitis, and the amount of intraoperative FFP administered were identified as possibly predictive variables, among which female sex and the amount of intraoperative FFP were identified as independent risk factors by multivariable analysis. Hendriks et al [10] and Kappa et al [13] reported that intraoperative blood loss predicted early reoperation. Child-Pugh class C and the amount of intraoperative FFP, which represent poor recipient liver function and have been associated with poor recipient outcome [24] , [25] , can reasonably be associated with early reoperation after liver transplantation, although, to the best of our knowledge, this is the first report demonstrating a higher early reoperation rate in more seriously ill recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, liver transplantation may also cause excessive blood loss during surgery, which may lead to increased postoperative morbidity and mortality. 89 There are several approaches available to attempt to reduce intraoperative blood loss, as will be outlined below.…”
Section: Prevention and Treatment Of Bleedingmentioning
confidence: 99%